Assessing the Effectiveness of an Educational Intervention on Organ Donation Awareness Among Undergraduate Students - Ashly T. John (International Journal of Evidence Based Nursing And Practices, 2026)
Organ donation continues to be critically low in India despite a growing demand for transplantable organs. Limited awareness, misconceptions, and negative perceptions contribute significantly to this gap. This study was conducted to evaluate the impact of an informational booklet on enhancing knowledge and shaping perceptions about organ donation among undergraduate students. A pre-experimental design with a one-group pretest–posttest approach was used, including 60 students selected through convenience sampling. Initially, participants’ baseline knowledge and perceptions were assessed using a structured questionnaire. Following this, an educational booklet on organ donation was provided as an intervention. A post-intervention assessment was then carried out to measure any changes. The results demonstrated a notable increase in knowledge levels, with mean scores rising from 50.39% before the intervention to 68.11% afterward. This improvement was found to be statistically significant (t = 7.85, p .
Keywords: Knowledge; Organ donation; information booklet; perception; undergraduate students